2018
DOI: 10.1080/17461391.2018.1450899
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pacing strategy on marathon world records

Abstract: The aim of this study was to analyse the influence of the pacing strategy adopted by elite marathon runners when setting every marathon world record in the last 50 years. We divided former marathon record holders into two groups: classic athletes (record holders between 1967 and 1988) and contemporaneous athletes (record holders between 1988 and 2018). The total distance of the marathon was divided into 8 sections of 5 km and 1 last section of 2.195 km, and the relative average speed of each section was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 42 publications
(49 reference statements)
2
55
2
3
Order By: Relevance
“…Involving more variables would require a larger test sample [47]. In future studies, the authors plan to consider specific running strategies, which is an important factor influencing the marathon running time [48]. Moreover, runners' experience and performance level should also be taken into account as they vary significantly among competitors over 50 years of age [49].…”
Section: Discussionmentioning
confidence: 99%
“…Involving more variables would require a larger test sample [47]. In future studies, the authors plan to consider specific running strategies, which is an important factor influencing the marathon running time [48]. Moreover, runners' experience and performance level should also be taken into account as they vary significantly among competitors over 50 years of age [49].…”
Section: Discussionmentioning
confidence: 99%
“…A better pacing strategy could provide elite marathon runners with an economical pathway to significant performance improvements at world-record level ( Angus, 2014 ). Pacing has evolved during the last 50 years, record holders between 1967 and 1988 started significantly faster, although after 25 km, their speed dropped dramatically and was significantly slower than in record holders between 1988 and 2018 ( Diaz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that winners in marathons run an even pace throughout the race ( Haney and Mercer, 2011 ; Breen et al, 2018 ; Diaz et al, 2018 ), whereas runners of lesser ability slowed as the race progressed, particularly after 20–25 km ( Ely et al, 2008 ). In addition, faster marathoners tend to run at a more consistent pace compared with slower runners ( March et al, 2011 ), whereas slower marathon finishers had greater variability of pace compared to faster marathoner finishers ( Haney and Mercer, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the pace profiles of the runners with Marathon World record showed a positive structure in the past years, in more current records, in the last 5 kilometers of this race, which was the fastest part, they began to change towards negative profiles. However, strategies characterized by minimum speed changes are indicated to be the most effective pacing strategies (6). From this point of view, differentiation of the results of this research from the pace profiles shows that the İstanbul Marathon is open to change and development in terms of pace profiles and pacing strategies.…”
Section: Discussionmentioning
confidence: 80%